Effect of corrective exercise program on the ground reaction force of student with flat food during gait cycle - Mostafa Payandeh; Nahid Khoshraftar; Ahmad Ebrahimi atri; Mohsen Damavandi (Vesnu Publications, 2014)
Abstract Introduction: In Some individuals because of the poor functioning leg muscles, plantar arch drooping suffered and it seems that ground reaction force individuals with flat foot than to those with normal foot, due to reduced recruitment is altered by the arc. The aim of  the present study the effect of corrective exercise program on the ground reaction force of student with flat food during gait cycle. Materials and Methods: In this study, 30 subjects with flat foot deformity the randomly and homogeneously divided in both intervention and control groups. Flat feet was measured by navicular droop test.The intervention group participated corrective exercises in 24 sessions of two months. Force plate apparatus for measuring ground reaction force were used before and after corrective exercises. For statistical analysis was used of parametric independent t-test and paired sample t-test (P ≤0/05). Results: The results showed that the vertical component of ground reaction in time weight transfer on the heel (P=0/01) and  toe weight transfer (P=0/03) stance phase in the intervention group after 8 weeks corrective exercises decreased significantly. But no significant difference in midstance phase between the two groups (P>0/05). Conclusion: Found on the basis of this study it can be concluded, corrective exercise can, performance increases of the plantar arch to absorb the force and reduces ground reaction force in subject  with flat foot  in two step, transfer weight on the heel and toe weight transfer on toe. Keywords: Flat foot, corrective exercises, Force plate, Ground reaction force, Student.